Population density and distance to market does not influence the farmers use of organic manure. - Olayide, O.; Alene, A.; Ikpi, A.; Nziguheba, Generose (2008)
This study developed and employed a socio-economic-ecological-modeling (SEEM) framework in its analyses. The SEEM is made up of four resource use domains of highlow population density and highlow access to market and two agro-ecologies in the savanna of Nigeria. Data used comprises a sample of 320 farm households in northern Nigeria. The pattern of organic manure use varied slightly and insignificantly across agro-ecological and resource use domains. The major finding of the study is that the resource use domains made use of same amount of organic manure. The level of organic manure use is, however, below the recommended levels for the cereal-based production systems in the study area. Policy that encourages the intensity of manure use and crop-livestock integration is recommended to support integrated soil fertility management practices in the study area.